The extended case method : four countries, four decades, four great transformations, and one theoretical tradition - Burawoy, Michael (University of California Press, 2009)
In this collection of essays, Burawoy develops the extended case method by connecting his own experiences among workers of the world to the great transformations of the 20th century including the rise and fall of the Soviet Union and its satellites, and the reconstruction of US capitalism.